Pengaruh Metode Outdoor Learning Terhadap Minat Belajar Siswa dalam Mata Pelajaran IPA Sekolah Dasar - Nurhafizah; Mustika, Dea (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The influence of the Outdoor Learning method on students' interest in learning science subjects in grade III of SD 023 Pandau Jaya. The formulation of the problem in this study "Seeing that there is an influence of Outdoor Learning on students' interest in learning science subjects in grade III of SD 023 Pandau Jaya" So as to find the goal of knowing whether or not there is an influence of the Outdoor Learning method on learning interest. This study is a quantitative study with a pre-experimental design type. The population in this study were all grade III students totaling 33 students. One group Pretest and posttest design were used for sampling. This study used a t-test which obtained the results α = 0.05> sig 0.000 with a significance level of 5%. So the hypothesis is accepted, with the conclusion that there is an influence of the Outdoor Learning method on students' interest in learning science subjects in grade III of SD 023 Pandau Jaya.